A review of technologies for in-situ sulfide control in anaerobic digestion. (April 2022) - Jung, Heejung; Kim, Danbee; Choi, Hyungmin; Lee, Changsoo
Abstract: The generation of toxic, malodorous, and corrosive hydrogen sulfide (H2 S), which can cause serious hygiene and health problems and damage biogas plants, is inevitable in anaerobic digestion (AD) of organic waste. H2 S is directly toxic to different microorganisms involved in AD, and sulfidogenesis competitively inhibits methanogenesis. Many technologies for ex-situ and in-situ sulfide removal have been developed for biogas cleaning. In-situ technologies that control sulfide within digesters do not require separate facilities and thus are more convenient and economical than ex-situ technologies. However, in-situ sulfide control during AD is directly affected by digester operating conditions and environmental factors, complicating its effective operation and leads to suboptimal performance. This paper reviews the principles, advantages, and disadvantages of different in-situ sulfide control technologies, from conventional to state-of-the-art. Although conventional technologies are technically simple and effective, their large-scale application has practical limitations related to high energy and chemical consumption and the need for sophisticated operation of digesters. Recently, several advanced technologies with promising potential have been developed to overcome these limitations, although there is still a long way to go for their practical application. In addition to better performance, the advanced technologies provide attractive possibilities to improve the economic feasibility for large-scale application by regenerating and recycling valuable materials and/or recovering elemental sulfur (S 0 ). Sulfide control is critical not only for biogas cleaning but also for stable digester operation, and it is receiving increasing attention as the importance of AD as an alternative energy source is growing. Given the increasing demand for more sustainable biogas production and upgrading, more research is needed to evaluate and improve the practical applicability of the advanced in-situ sulfide control technologies in anaerobic digester environments, particularly at large scale. This review also discusses the key challenges for their practical application and suggests future research directions. Graphical abstract: Image 1 Highlights: H2 S production is an inevitable problem in anaerobic digestion of organic waste. In-situ sulfide control can be a convenient and economical way to clean biogas. Principles, advantages, and disadvantages of different technologies are reviewed. Recent advances and future challenges in in-situ sulfide control are discussed. Future studies to assess the practicability of advanced technologies are proposed.